2019
DOI: 10.1080/00268976.2019.1652366
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effects in liquid water via deep potential molecular dynamics

Abstract: A comprehensive microscopic understanding of ambient liquid water is a major challenge for ab initio simulations as it simultaneously requires an accurate quantum mechanical description of the underlying potential energy surface (PES) as well as extensive sampling of configuration space. Due to the presence of light atoms (e.g., H or D), nuclear quantum fluctuations lead to observable changes in the structural properties of liquid water (e.g., isotope effects), and therefore provide yet another challenge for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 101 publications
1
73
0
Order By: Relevance
“…As a remedy, several studies have been performed by training an MLP using higher rungs of KS-DFT (e.g., hybrid-DFT or meta-GGA) and then using this potential in PIMD simulations. 575 , 579 581 The study of water mentioned in the previous section, which used MLPs trained from hybrid DFT, revealed that NQEs were critical for promoting the hexagonal packing of molecules inside ice that ultimately lead to the 6-fold symmetry of snowflakes. 575 Highly data efficient ML potentials can even be trained on reference data at the computationally very expensive quantum-chemical CCSD(T) level of accuracy.…”
Section: Applications Of Machine Learning To Chemical Systemsmentioning
confidence: 99%
“…As a remedy, several studies have been performed by training an MLP using higher rungs of KS-DFT (e.g., hybrid-DFT or meta-GGA) and then using this potential in PIMD simulations. 575 , 579 581 The study of water mentioned in the previous section, which used MLPs trained from hybrid DFT, revealed that NQEs were critical for promoting the hexagonal packing of molecules inside ice that ultimately lead to the 6-fold symmetry of snowflakes. 575 Highly data efficient ML potentials can even be trained on reference data at the computationally very expensive quantum-chemical CCSD(T) level of accuracy.…”
Section: Applications Of Machine Learning To Chemical Systemsmentioning
confidence: 99%
“…that can be used to learn complex highdimensional PES via machine learning (ML) based approaches. [17][18][19][20] Assuming that the system is ergodic, the accuracy of a given MD simulation in predicting equilibrium properties is primarily governed by the quality of the ionic forces and stress tensor (or cell forces) used when propagating the corresponding equations of motion. As such, a physically sound approach for obtaining these forces is given by first-principles based electronic structure theories, which are the foundation for ab initio MD (AIMD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…21 In this work we extend both the time and length scales sampled by AIMD using a deep neural network (DNN) to represent the potential energy surface (PES), gaining a substantial speed-up of MD simulations. Several authors have demonstrated the DNNs' ability to reproduce the complex PES of ab initio potentials, [32][33][34] thus allowing accurate long-time simulations of several condensed phase systems [35][36][37] including metal oxide-water interfaces. 38,39 In the present study, the ab initio-based DNN potential reproduces energy and atomic forces obtained from DFT at a ve orders of magnitude lower computational cost.…”
Section: Introductionmentioning
confidence: 99%